The effect of morphological intervention on EFL students' morphological awareness, vocabulary knowledge and listening comprehension - Shuping, Chen (2025)
Despite the increasing importance of listening comprehension in Chinese university students’ English learning as a foreign language (EFL), their listening proficiency is much lower compared with reading and writing skills. Abundant research show that this problem is largely due to inadequacy of their vocabulary knowledge. One potential strategy of vocabulary development is conducting morphological intervention. Additionally, morphological awareness helps to process and comprehend the spoken discourse because phonological, syntactic, and semantic information are carried in morphemes. This study aimed to investigate the roles of morphological intervention on EFL university learners’ morphological awareness, four measures of vocabulary knowledge (written vocabulary breadth, written vocabulary depth, aural vocabulary breadth, and aural vocabulary depth), and listening comprehension and how these four measures of vocabulary knowledge mediate between morphological awareness and listening comprehension. An experimental group (n = 32) and a control group (n = 32) of second-year business English majors in a Chinese university participated in this quasi-experimental quantitative study. Only the experimental group received ten sessions of morphological intervention. Both groups sat for the pre and post-tests to collect data analyzed by SPSS version 27 and Smart PLS 4.0. Findings of MANOVA analysis of the pretests and posttests indicated that morphological intervention was successful in improving EFL university students’ morphological awareness, four measures of vocabulary knowledge, and listening comprehension. The findings of PLSSEM analysis showed that the four measures of vocabulary knowledge collectively and significantly mediated the relationship between morphological awareness and listening comprehension. Specifically, both aural vocabulary breadth and depth functioned as individual and significant mediators, while written vocabulary breadth and depth did not show such mediating effects. The study suggests that teaching morphology plays a significant role in enhancing EFL university students’ written and aural vocabulary and listening comprehension. Hence, the study could serve as a base for future morphological interventions.